A Sociolinguistic Analysis Study of Taboo Words Found in K-12 The Film - Alma Meyla Putri, Ni Putu; Gde Sosiowati, I Gusti Ayu; Widhiarcani Matradewi, Ni Ketut (Udayana Journal of Social Sciences and Humanities, 2022)
This study which entitled A Sociolinguistic Analysis Study of Taboo Words Found in K-12 The Film that is aimed to find out the types of taboo words found in the film and analyze the functions of uttering those taboo words. The data of this study were obtained from K-12 The Film, which directed by Melanie Martinez and co-directed by Alissa Torvinen. The data were obtained using the documentation method and a note-taking technique and it is taken from the character’s conversation and from the song lyrics that are appeared in the movie. This study uses a descriptive qualitative method with the theory from Battistella (2005:72) on the types of taboo words and the theory from Wardhaugh (2006:239) on the functions of uttering taboo words.